B12
1) (x+2)2+2(x+1)
=(x2+4x+4)+2x+2
= (x^2 + 4x + 4) + 2x + 2
=(x2+4x+4)+2x+2
=x2+4x+4+2x+2
= x^2 + 4x + 4 + 2x + 2
=x2+4x+4+2x+2
2) (x−4)+(x+1)(x+2)
=x−4+(x2+2x+x+2)
= x - 4 + (x^2 + 2x + x + 2)
=x−4+(x2+2x+x+2)
=x−4+x2+3x+2
= x - 4 + x^2 + 3x + 2
=x−4+x2+3x+2
=x2+4x−2
= x^2 + 4x - 2
=x2+4x−2
3) (x−y)2+2x(x+y)
=x2−2xy+y2+2x2+2xy
= x^2 - 2xy + y^2 + 2x^2 + 2xy
=x2−2xy+y2+2x2+2xy
=x2−2xy+y2+2x2+2xy
= x^2 - 2xy + y^2 + 2x^2 + 2xy
=x2−2xy+y2+2x2+2xy
=3x2+y2= 3x^2 + y^2
=3x2+y2
4) 3(x+1)+(x+1)2
=3x+3+(x2+2x+1)
= 3x + 3 + (x^2 + 2x + 1)
=3x+3+(x2+2x+1)
=3x+3+x2+2x+1
= 3x + 3 + x^2 + 2x + 1
=3x+3+x2+2x+1
=x2+5x+4
= x^2 + 5x + 4
=x2+5x+4
5) (x+5)2x−(x−3)2
=2x2+10x−(x2−6x+9)
= 2x^2 + 10x - (x^2 - 6x + 9)
=2x2+10x−(x2−6x+9)
=2x2+10x−x2+6x−9
= 2x^2 + 10x - x^2 + 6x - 9
=2x^2+10x−x^2+6x−9
=x^2+16x−9= x^2 + 16x - 9
=x^2+16x−96)x(4x+3y)−2x−(y−2x)^2
=4x^2+3xy−2x−(y^2−4xy+4x^2)
= 4x^2 + 3xy - 2x - (y^2 - 4xy + 4x^2)=4x^2+3xy−2x−(y^2−4xy+4x^2)
=4x^2+3xy−2x−y^2+4xy−4^x2
= 4x^2 + 3xy - 2x - y^2 + 4xy - 4x^2
=4x^2+3xy−2x−y^2+4xy−4x^2
=7xy−y^2−2x= 7xy - y^2 - 2x
=7xy−y^2−2x
7) (7x−1)(x+2)−(x+4)^2
=(7x^2+14x−x−2)−(x^2+8x+16)
= (7x^2 + 14x - x - 2) - (x^2 + 8x + 16)
=(7x^2+14x−x−2)−(x^2+8x+16)
=7x^2+13x−2−x^2−8x−16
= 7x^2 + 13x - 2 - x^2 - 8x - 16
=7x^2+13x−2−x^2−8x−16
=6x^2+5x−18= 6x^2 + 5x - 18
=6x^2+5x−18
B13